Prevention of dendrite growth and volume expansion to give high-performance aprotic bimetallic Li-Na alloy–O2 batteries - Ma, Jin-ling; Meng, Fan-lu; Yu, Yue; Liu, Da-peng; Yan, Jun-min; Zhang, Yu; Zhang, Xin-bo; Jiang, Qing (Nature chemistry, 2019)
Rechargeable aprotic alkali metal (Li or Na)–O 2 batteries are the subject of great interest because of their high theoretical specific energy. However, the growth of dendrites and cracks at the Li or Na anode, as well as their corrosive oxidation lead to poor cycling stability and safety issues. Understanding the mechanism and improving Li/Na-ion plating and stripping electrochemistry are therefore essential to realizing their technological potential. Here, we report how the use of a Li-Na alloy anode and an electrolyte additive realizes an aprotic bimetal Li-Na alloy–O 2 battery with improved cycling stability. Electrochemical investigations show that stripping and plating of Li and Na and the robust and flexible passivation film formed in situ (by 1,3-dioxolane additive reacting with the Li-Na alloy) suppress dendrite and buffer alloy anode volume expansion and thus prevent cracking, avoiding electrolyte consumption and ensuring high electron transport efficiency and continued electrochemical reactions. The use of Li or Na as electrodes in Li-Na alloy–O 2 batteries creates formidable challenges for both safety and stability because of their oxidative corrosion and the growth of dendrites and cracks on their surface. Now, an aprotic bimetal Li-Na alloy–O 2 battery with high cycling stability has been developed using a Li-Na eutectic alloy anode and an electrolyte additive.